A human-machine interface analysis: Under critical operation scenario - Rehder, Ivan de Souza; Sarmento, Andrew; Russo, Ana Carolina; Cardoso Junior, Moacyr Machado; Villani, Emilia (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
This study investigates the impact of the human-machine interface (HMI) on decision-making and Command and Control for Unmanned Aerial Systems (UAS). Using a prototype HMI simulating UAS in combat scenarios, we evaluate human performance through physiological sensors to identify trends in the relationship between HMI factors, decision-making, and system performance. The objective is to develop optimized HMI designs that reduce cognitive workload, improve decision-making, and enhance situational awareness during critical operations. The findings have implications for controlling Unmanned Aerial Vehicles (UAVs) in surveillance, search and rescue, and military operations, enhancing operational effectiveness and safety.